Perpendicular implantation of porcine trachea extracellular matrix for enhanced xenogeneic scaffold surface epithelialization in a canine model - Kato, Ayumu; Go, Tetsuhiko; Otsuki, Yasuhiro; Yokota, Naoya; Soo, Chang Sung; Misaki, Noriyuki; Yajima, Toshiki; Yokomise, Hiroyasu (Frontiers in Surgery, 2023)
Objective: The availability of clinically applied medical materials in thoracic surgery remains insufficient, especially materials for treating tracheal defects. Herein, the potential of porcine extracellular matrix (P-ECM) as a new airway reconstruction material was explored by xenotransplanting it into a canine trachea. Methods: P-ECM was first transplanted into the buttocks of Narc Beagle dogs (n=3) and its overall immuno-induced effects were evaluated. Subsequently, nine dogs underwent surgery to create a tracheal defect that was 1×2 cm. In group A, the P-ECM was implanted parallel to the tracheal axis (n=3), whereas in group B the P-ECM was implanted perpendicular to the tracheal axis (n=6). The grafts were periodically observed by bronchoscopy and evaluated postoperatively at 1 and 3 months through macroscopic and microscopic examinations. Immunosuppressants were not administered. Statistical evaluation was performed for Bronchoscopic stenosis rate, graft epithelialization rate, shrinkage rate and ECM live-implantation rate. Results: No sign of P-ECM rejection was observed after its implantation in the buttocks. Bronchoscopic findings showed no improvement concerning stenosis in group A until 3 months after surgery; epithelialization of the graft site was not evident, and the ECM site appeared scarred and faded. In contrast, stenosis gradually improved in group B, with continuous epithelium within the host tissues and P-ECM. Histologically, the graft site contracted longitudinally and no epithelialization was observed in group A, whereas full epithelialization was observed on the P-ECM in group B. No sign of cartilage regeneration was confirmed in both groups. No statistically significant differences were found in bronchoscopic stenosis rate, shrinkage rate and ECM live-implantation rate, but graft epithelialization rate showed a statistically significant difference (G-A; sporadic (25%) 3, vs G-B; full covered (100%) 3; p=0.047). Conclusions: P-ECM can support full re-epithelialization without chondrocyte regeneration, with perpendicular implantation facilitating epithelialization of the ECM. Our results showed that our decellularized tracheal matrix holds clinical potential as a biological xenogeneic material for airway defect repair.